Ferdinand de Saussure's Structuralism Theory and Its Relevance in Arabic Language Learning - Amal, Adi Ihsanul; Setiyawan, Agung (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
Saussure's theory of structuralism provides an important foundation in linguistics, with concepts such as cyclic and diachronic, langue and parole, signifiant and signifié, and syntagmatic and paradigmatic dimensions, which are relevant in Arabic language learning to understand the structure and use of language. The purpose of this study is to find out how relevant Ferdinand de Saussure's theory is in Arabic language learning. The method presented in this research is titled library research. So that the data obtained comes from Ferdinand de Saussure's structuralism theory and Arabic language learning. The results of this study show that the application of Saussure's structuralism theory in Arabic language learning helps students to understand the language system as a whole, enriching their understanding of language structure and contextual language use.